2014
DOI: 10.1590/1982-021620146713
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome metabólica e associação com nível socioeconômico em escolares

Abstract: Objetivo verificar a associação entre o nível socioeconômico e a presença de síndrome metabólica (SM) em escolares da rede pública da cidade de Montes Claros-MG. Métodos trata-se de estudo transversal, analítico. Foram avaliados 382 escolares entre 10 e 16 anos, a partir da amostragem por conglomerados. A condição socioeconômica foi dividida em alta e baixa e a SM foi diagnosticada utilizando os critérios da International Diabetes Federation. Para análise dos dados, utilizou-se o teste qui-quadrado (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
2
0
2
Order By: Relevance
“…In this context, Metabolic Syndrome (MS) has gained prominence, since it results from the meeting of several cardiovascular risk factors (CRF), such as systemic arterial hypertension (SAH), disorders of glucose and lipid metabolism, and visceral obesity [3]. However, its study has been hampered by the lack of conformity in its definition.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Metabolic Syndrome (MS) has gained prominence, since it results from the meeting of several cardiovascular risk factors (CRF), such as systemic arterial hypertension (SAH), disorders of glucose and lipid metabolism, and visceral obesity [3]. However, its study has been hampered by the lack of conformity in its definition.…”
Section: Introductionmentioning
confidence: 99%
“…Also, being a member of lower income families is associated with the incidence of and mortality for cardiovascular diseases, probably due to the combination of risk factors. 32 Although the purpose of the present study was not to analyze specific diagnosis of the study population, Gonçalves et al, 22 have reported the high prevalence of anxiety disorders in Brazil and attribute this finding to the generalized urban violence and adverse socioeconomical conditions. Besides, the high levels of noise and the lack of recreational areas in Brazilian big cities may be also be related.…”
Section: Discussionmentioning
confidence: 71%
“…No estudo do ERICA, verificou-se uma maior prevalência de SM nos estudantes de escolas públicas, o que pode indicar uma possível associação do nível socioeconômico com a SM [7]. Em Montes Claros, Minas Gerais, Cruz et al [32], ao avaliarem 382 estudantes de 10 a 16 anos, encontraram maior prevalência de SM (8,70%) entre os adolescentes de classe socioeconômica mais baixa. No entanto, quanto ao estado nutricional, estudos brasileiros verificaram a existência de uma associação entre o maior nível socioeconômico e a presença de excesso de peso [33,34].…”
Section: Discussionunclassified